The identity of Cromapanax and lectotypification of C. lobatus (Araliaceae) - Deng, Yunfei; Tong, Yi (Phytotaxa, 2022)
The herbarium sheet cited as the holotype of Cromapanax lobatus (Araliaceae) contains two distinct elements belonging to two different families. The vegetative part is identical with Clerodendrum hastatum of Lamiaceae and the fruiting part is Macropanax undulatus of Araliaceae. The fruiting part, one of these elements, is designated as the lectotype for the name Cromapanax lobatus.